Generation and characterization of a novel gne Knockout Model in Zebrafish - Livne, Hagay; Avital, Tom; Ruppo, Shmuel; Harazi, Avi; Mitrani-Rosenbaum, Stella; Daya, Alon (Frontiers in Cell and Developmental Biology, 2022)
GNE Myopathy is a rare, recessively inherited neuromuscular worldwide disorder, caused by a spectrum of bi-allelic mutations in the human GNE gene. GNE encodes a bi-functional enzyme responsible for the rate-limiting step of sialic acid biosynthesis pathway. However, the process in which GNE mutations lead to the development of a muscle pathology is not clear yet. Cellular and mouse models for GNE Myopathy established to date have not been informative. Further, additional GNE functions in muscle have been hypothesized. In these studies, we aimed to investigate gne functions using zebrafish genetic and transgenic models, and characterized them using macroscopic, microscopic, and molecular approaches. We first established transgenic zebrafish lineages expressing the human GNE cDNA carrying the M743T mutation, driven by the zebrafish gne promoter. These fish developed entirely normally. Then, we generated a gne knock-out (KO) fish using the CRISPR/Cas9 methodology. These fish died 8-10 days post-fertilization (dpf), but a phenotype appeared less than 24 hours before death and included progressive body axis curving, deflation of the swim bladder and decreasing movement and heart rate. However, muscle histology uncovered severe defects, already at 5 dpf, with compromised fiber organization. Sialic acid supplementation did not rescue the larvae from this phenotype nor prolonged their lifespan. To have deeper insights into the potential functions of gne in zebrafish, RNA sequencing was performed at 3 time points (3, 5, and 7 dpf). Genotype clustering was progressive, with only 5 genes differentially expressed in gne KO compared to gne WT siblings at 3 dpf. Enrichment analyses of the primary processes affected by the lack of gne also at 5 and 7 dpf point to the involvement of cell cycle and DNA damage/repair processes in the gne KO zebrafish. Thus, we have established a gne KO zebrafish lineage and obtained new insights into gne functions. This is the only model where GNE can be related to clear muscle defects, thus the only animal model relevant to GNE Myopathy to date. Further elucidation of gne precise mechanism-of-action in these processes could be relevant to GNE Myopathy and allow the identification of novel therapeutic targets.